2020
DOI: 10.3390/aerospace7120167
|View full text |Cite
|
Sign up to set email alerts
|

Constructive Aerodynamic Interference in a Network of Weakly Coupled Flutter-Based Energy Harvesters

Abstract: Converting flow-induced vibrations into electricity for low-power generation has received growing attention over the past few years. Aeroelastic phenomena, good candidates to yield high energy performance in renewable wind energy harvesting (EH) systems, can play a pivotal role in providing sufficient power for extended operation with little or no battery replacement. In this paper, a numerical model and a co-simulation approach have been developed to study a new EH device for power generation. We investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Researchers have demonstrated that the piezoelectric‐fluttering phase is the most dominant and efficient region of harvesting electrical energy for aerospace applications 38,39 . After the flutter‐velocity, a disturbance in the stability of the oscillations has been noticed which adversely affects the coupled load of the piezoelectric energy harvester 40,41 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated that the piezoelectric‐fluttering phase is the most dominant and efficient region of harvesting electrical energy for aerospace applications 38,39 . After the flutter‐velocity, a disturbance in the stability of the oscillations has been noticed which adversely affects the coupled load of the piezoelectric energy harvester 40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Researchers have demonstrated that the piezoelectricfluttering phase is the most dominant and efficient region of harvesting electrical energy for aerospace applications. 38,39 After the flutter-velocity, a disturbance in the stability of the oscillations has been noticed which adversely affects the coupled load of the piezoelectric energy harvester. 40,41 Therefore, a new concept of limit cycle oscillations 42 has been introduced to sustain those unstable oscillations, and over the past few years, this emerging concept has been widely used in aerospace applications for powering different sensors or MEMS devices from the harvested energy.…”
Section: Introductionmentioning
confidence: 99%
“…Wind tunnels are considered an important research tool for designing and evaluating aerospace vehicles [1,2], wind energy harvesters [3], bridges [4,5], automobiles [6], and buildings [7][8][9]. The current experimental investigations for energy harvesting are mainly conducted in larger volume wind tunnels.…”
Section: Introductionmentioning
confidence: 99%